DEVELOPMENT OF KOMIKU TEACHING MATERIALS BASED ON LOCAL WISDOM TO INCREASE THE INTEREST IN READING AND WRITING STUDENTS - Wahyu Nugroho; Ella Rahma Azizah; Diyanti Pratiwi (Jurnal Cakrawala Pendas, 2024)
Teaching materials have a very important role for teachers and students, especially for students with special needs. However, in reality there are still many schools that have not developed teaching materials. Apart from that, the average child with special needs also does not know and understand local wisdom, especially in Trenggalek Regency. This research aims to develop comic teaching materials based on local wisdom for students with special needs and test the effectiveness and validity of comic teaching materials based on local wisdom for students with special needs in grade 1 of elementary school. This research is a type of research and development (Research & Development) using the ADDIE development model. The stages of the ADDIE model include Analysis, Design, Development, Implementation and Evaluation. In this research, an instrument was used in the form of a questionnaire with data collection carried out through observation, interviews and questionnaires. Data analysis was carried out using qualitative analysis techniques and quantitative analysis. The results of this research show that comic teaching materials based on local wisdom are valid and practical to use in learning. Apart from that, the results of the paired sample t-test and N-Gain test show that there is an influence from the use of comic teaching materials based on local wisdom and included in the interpretation category which is quite effective. The conclusion of this research is that comic teaching materials based on local wisdom are quite effective and influential in increasing interest in reading and writing for students with special needs in grade 1 of elementary school.